Correlation of the base of the Serpukhovian Stage (Mississippian) in NW Europe - Sevastopulo, G.; Barham, Milo (Cambridge University Press, 2013)
The Task Group charged with proposing the GSSP for the base of the Serpukhovian Stage (Mississippian, Lower Carboniferous) is likely to use the global First Appearance Datum (FAD) of the conodont Lochriea ziegleri in the lineage Lochriea nodosa – L. ziegleri for the definition and correlation of the base of the stage. It is important to establish that the FAD of L. ziegleri in different basins is penecontemporaneous. Ammonoids provide high-resolution biostratigraphy in the Late Mississippian but their use in international correlation is limited by provincialism. However, it is possible to assess the levels of diachronism of the First Occurrence Datum (FOD) of L. ziegleri in sections in NW Europe using ammonoid zones. Published conodont distribution in the Rhenish Slate Mountains of Germany show the FOD of L. ziegleri in the Emstites novalis Biozone (upper part of the P2c zone of the UK and Ireland) but L. ziegleri has also been reported as occurring in the Neoglyphioceras spirale Biozone (P1d zone). In the Yoredale Group of northern England, the FOD of L. ziegleri is in either the P1c or P1d zone. In NW Ireland, the oldest records of both L. nodosa and L. ziegleri are from the Lusitanoceras granosum Biozone (P2a). Although there is some discrepancy in the recorded levels of the FOD of L. ziegleri in NW Europe, this may be as a result of collection failure. The base of the Serpukhovian based on the FAD of Lochriea ziegleri will be in the middle of the Brigantian regional Substage.